2020
DOI: 10.1038/s41467-020-15393-8
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of humidity in modeling summer electricity demand across the United States

Abstract: Cooling demand is projected to increase under climate change. However, most of the existing projections are based on rising air temperatures alone, ignoring that rising temperatures are associated with increased humidity; a lethal combination that could significantly increase morbidity and mortality rates during extreme heat events. We bridge this gap by identifying the key measures of heat stress, considering both air temperature and near-surface humidity, in characterizing the climate sensitivity of electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…This combined impact of temperature and humidity is better indicative of the physiological experience of heat, and the higher the humidity, the higher the perceived temperature, the higher the potential health risks, the poorer the thermal comfort, and hence, the higher the building energy use to keep the indoor conditions at favorable levels. Despite recent sporadic studies that demonstrated that humid heat is increasingly a global trend [11] and highlighted urban moisture as a prevalent issue and an aggravator of heat island impact [12][13][14][15] with important implications on health and energy use [16], the scholarly discourse on urban microclimate under current and future climatic trends is still heavily dominated by air temperatures alone. In this respect, our presuppositions with regards to the thermal comfort in different land-use areas need also to be revisited, especially in tropical and subtropical cities (compared to mid-latitude cities), because (1) high air temperatures and UHI in tropical and subtropical cities is an almost year-round critical phenomenon, (2) humidity levels are rather high due to frequent and intense precipitation, and (3) ventilation is low due to overall lower wind speed values, further exacerbating the adverse impact of humidity on perceived temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…This combined impact of temperature and humidity is better indicative of the physiological experience of heat, and the higher the humidity, the higher the perceived temperature, the higher the potential health risks, the poorer the thermal comfort, and hence, the higher the building energy use to keep the indoor conditions at favorable levels. Despite recent sporadic studies that demonstrated that humid heat is increasingly a global trend [11] and highlighted urban moisture as a prevalent issue and an aggravator of heat island impact [12][13][14][15] with important implications on health and energy use [16], the scholarly discourse on urban microclimate under current and future climatic trends is still heavily dominated by air temperatures alone. In this respect, our presuppositions with regards to the thermal comfort in different land-use areas need also to be revisited, especially in tropical and subtropical cities (compared to mid-latitude cities), because (1) high air temperatures and UHI in tropical and subtropical cities is an almost year-round critical phenomenon, (2) humidity levels are rather high due to frequent and intense precipitation, and (3) ventilation is low due to overall lower wind speed values, further exacerbating the adverse impact of humidity on perceived temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…These three utilities combine to provide electricity to over 95% of Californians 30 . We consider the daily variation of both dry-bulb (T) and wet-bulb (W) temperatures in our analysis, following previous studies showing the importance of T and humidity (embedded in W), affecting electricity consumption patterns across US 3 . Both climatic variables are aggregated to an equivalent geographic scale of the electricity data using population as a spatial weighting factor ("Methods").…”
mentioning
confidence: 99%
“…The air temperature is considered one of the most important climate factors, as the daily activities of people are influenced by even a minor change in air temperature 13 . According to Maia-Silva et al 14 , relative humidity (RH; calculated from the surface air and dew point temperatures) rise is one of the main climate challenges, as the increase in surface air temperature is correlated with a decrease in relative humidity. This coupling effect can be disastrous, especially during heat wave events.…”
Section: Introductionmentioning
confidence: 99%